PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI PROGRAM KOTAKU / PNPM DI KECAMATAN CIAWI - Rohimat, Dadan; Rahmawati, Rita; Seran, G. Goris (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2017)
The background of this research based on constitution article 27 paragraph 2 which states that âevery citizen is entitled to work and means appropriate for humanity â. Several steps are taken by a government in implementing this law such as the national program of community empowerment like KOTAKU/PNPM. Generally, there are contemporary issues in development such as Human Development Index (HDI), Poverty , Justice and Social Equality and accordingly there are strategic issues in the Bogor area such as Â Human Development Index is still low, marked by unemployment and poverty rate is still high and although Bogor has sufficient natural resources and competitive , but not yet been explored optimally. Thefore, it is important to discuss the participation of theÂ program KOTAKU / PNPM as a form of community involvement to resolve these issues. KOTAKU Program use synergy platform the collaboration of local government and other stakeholders in the district and community-based infrastructure development to accelerate the handling of urban slum problems.The formulation problem are how public participation of the program KOTAKU/ PNPM, what problem occured and influenced the program, and what efforts are taken to solve the problem. The purpose of research are to understand the extent of effectiveness of the KOTAKU program and the level of participation from general public. According to Cohen and Uphoff, as cited by Siti Irene Astuti (2011: 61-63) distinguish participation can be devided into four types: (1) participation in decision making, (2) participation in the implementation, (3) participation in the utilization, and (4) participation in evaluation. Some factors that affects participation namely benefit of activities, an opportunity, skill, a feeling of ownership and community figures. Meanwhile, the implementation is action performed either by individuals or groups or government officials or private directed at the achievement of the some of the causes that have determined in the policy decision (Van Meter and Van Horn, 1975. In addition, policy implemenentation theory proposed by George C.Edwards III (1980) states that policy implementation is influenced by four variable as follow : (1). Communication, (2). Resources, (3). Disposition/Attitude, and (4). Bureaucratic Structure.Research methodology used is quantitative descriptive, technique of data collection and data analysis use primary and secondary data based on observation technique , the questionnaire and interview , and thenÂ processed into the form of figures to do statistic calculation to draw conclusion. The sampling technique used is proportional random sampling in accordance to Solvinâs formula , and obtained samples of 100 respondents , with reference to productive ages .Based on the research it can be concluded that based on the calculation on those dimensions of public participation in Ciawi district has a value of 3.72 and intepreted as âgoodâ category. With the conditions of Ciawi district which is so vast, potential large enough of religious communities, but still high poverty rate and many things to be improved and could not be separated from public participation in developing their areas. But there are several things must be done to increase, among others as follow :Socialization should be increased , that intention and purposes can be implemented and in accordance with the target.Optimalitazing society organizations in the each area/Village.Budget transparancy is needed to maintain of public trust.Â Keywords : Participation, Implementation, Program